Micro-Scale Variability Impacts the Outcome of Competition Between Different Modeled Size Classes of Phytoplankton - Mandal, Sandip; Smith, S. Lan; Priyadarshi, Anupam; Yamazaki, Hidekatsu (Frontiers in Marine Science, 2019)
Previous modelling studies have shown that observed micro-scale (mm) variability of nutrients and phytoplankton biomass can strongly impact the large-scale mean growth response of phytoplankton in ways that cannot be represented by typical models based on the mean field approximation. Also, models accounting for the flexible eco-physiology of phytoplankton predict quite different responses to changing environmental conditions compared to most current (inflexible) models. Combining these two ideas for nutrient-phytoplankton systems we have developed a new ‘Flexible NP closure model’ to represent competition among the three typically observed phytoplankton size classes: pico-, nano-, and microphytoplankton. Both micro-scale variability and flexible eco-physiology are expected to impact the competition among these size classes. With this work we began to address how both these factors determine the size diversity of phytoplankton in the ocean. Under eutrophic conditions, variability did not impact the modeled growth rate of any size class. On the other hand, under oligotrophic conditions, variability preferentially enhanced micro-size biomass, and reduced the biomass of both nano- and pico-size classes.